Does Self-control Outdo IQ in Predicting Academic Performance? - Vazsonyi, Alexander T; Javakhishvili, Magda; Blatny, Marek (Journal of youth and adolescence, 2022)
Duckworth and Seligman's seminal work found that self-discipline (self-control) was more salient for academic achievement than intelligence. Very little replication work exists, including in different cultures; the current study addressed these gaps. Data were collected from 6th and 7th grade cohorts of early adolescents (N = 589; age: Mean = 12.34 years, and SD = 0.89; 58% female) over two years. The study tested whether self-control was a stronger predictor than intelligence in explaining academic performance two years later as well as in explaining developmental changes over the course of two years. Path analyses provided evidence that both self-control and intelligence longitudinally predicted teacher-reported academic competence as well as school-reported grades; however, intelligence was a significantly stronger predictor than self-control. In addition, only intelligence predicted developmental changes in each measure of academic performance over time, self-control did not.
Keywords: Male; Intelligence; inteligence; Achievement; Schools; školní úspěšnost; Academic achievement; Humans; stupeň vzdělání; mužské pohlaví; Female; Educational Status; mladiství; sebekontrola; ženské pohlaví; Individual differences; úspěšnost; Self-discipline; školy; Academic Success; Adolescent; lidé; dítě; Child; Self-Control